USE OF PUBLIC PRIVATE PARTNERSHIP IN THE IMPLEMENTATION OF PUBLIC POVERTY REDUCTION PROGRAMS (American Journal of Business Management, Economics and Banking, 2025)
The article reveals the possibilities and problems of using public-private partnerships in the implementation of state programs to reduce poverty. In the implementation of state programs to reduce poverty, problems are associated, first of all, with the lack of financial resources of public funds. Today, cooperation between the public and private sectors forms an effective mechanism for attracting investments aimed at ensuring economic growth and reducing poverty.